MARKET REACTION BEFORE AND AFTER STOCK SPLIT - Garnis Irawanti; Deky Prasetyo; Bio Ertanto; Mohamad Bastomi; Amalia Anggrayni (Bajang Institute, 2025)
The issuer believes that with the high stock price, it can make investors uninterested. Therefore, efforts that can be made by conducting a stock split which is based on the Trading Range Theory where the market assumes that by conducting a stock split it can keep stocks from being too expensive and more investors will invest. Signaling Theory states that a stock split is a tool for conveying more information about the company's prospects. This study aims to obtain empirical evidence regarding the comparison of Trading Volume Activity and Abnormal Return before and after the stock split announcement. The results of the Wilcoxon signed ranks test on the average Trading Volume Activity five days before and five days after the Stock split showed that there was a significant difference, while the results of the Paired Sample T-test for Abnormal Return showed a difference five days before and five days after the stock split. Based on the results of the study above, it can be concluded that there is a significant difference in Trading Volume Activity and Abnormal Return before and after the Stock Split. The suggestion that can be conveyed in this study is that not all information provided is valuable information so investors need to be able to sort out information as a consideration in decision making